Jane Tolmach Press Release
This press release, titled "Tolmach Substantiates Charges on Opponent's Finances," reiterates Jane Tolmach's claim that a large majority of her opponent Charles Imbrecht's campaign funds come from out-of-county special interests. She argues that, using his own reported totals and including forgiven loans and non-monetary contributions, at least 68% of his funding derives from outside Ventura County sources, contradicting his claim that only 36% does. The release lists specific contributors—including political action committees, corporations, the Republican State Central Committee, and "United for California"—to support her charge of heavy special-interest backing. Tolmach further notes that only 7% of Imbrecht's contributions were under $50 compared to 42% of hers, portraying her campaign as more locally and grassroots funded. She also states that she intends to divest any stock holdings that could present a conflict of interest if elected.